In vitro food production from animal cell cultures as a meat alternative (selected legal aspects) - Leśkiewicz, Katarzyna (Przegląd Prawa Rolnego, 2019)
From a legal point of view, there may be doubts as to the legal qualification of food obtained in vitro from animal cells. An opinion is expressed in the article that meat from animal cells obtained using the in vitro method does not fall within the classical legal concepts of meat or agricultural production. However, meat products from cells produced by the in vitro method may satisfy the criteria established for novel food. If this is considered to be the correct way of qualification, then they should be subject to the EU market authorisation procedure regulated in Regulation 2015/2283, and a subsequent assessment of their safety. From a legal, economic and social point of view, it is reasonable to produce food using atypical methods if these methods are capable of ensuring food safety.